PEMBAGIAN HASIL PERKEBUNAN KARET DI DESA GALING: TINJAUAN ATAS PRINSIP MUSAQAH DALAM KOMPILASI HUKUM EKONOMI SYARIAH - Silma Sawali; Syahbudi Syahbudi; Nur Rahmiani (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2025)
This study aims to determine the implementation of the musaqah contract in the KHES review of cooperation for the production sharing of rubber plantation maintenance in Galing Village. This research uses qualitative research methods with a type of field research and a normative sociological paradigm approach. The data source uses primary data obtained from interviews with the owners and managers in Galing Village. The people of Galing Village rely heavily on the agricultural sector for economic growth. The agricultural sector is one of the sectors that greatly contributes to the economy in Galing Village. Plantation crops, namely rubber plantations, are one of the agricultural subsectors that can help meet the economic needs of the people of Galing Village. The owner and manager of the rubber plantation in Galing Village collaborate on the production sharing of rubber plantations with an oral agreement and use a musaqah contract. The pattern of profit sharing is based on the initial agreement, namely, using a profit-sharing system based on production results, with as much as 1/3 of the harvest. In the implementation of this profit sharing, there is a default committed by the owner against the manager by reducing the profit sharing for the manager. However, the implementation of this agreement violates the law of musaqah. This is because there is a reduction in profit sharing that is detrimental to the manager. According to Musaqah in the Compilation of Sharia Economic Law regarding the division of plantation yields, there is a violation of Musaqah law.